Novel Lactobacillus reuteri HI120 Affects Lipid Metabolism in C57BL/6 Obese Mice - Sun, Ye; Tang, Yanqing; Hou, Xufeng; Wang, Hesong; Huang, Liuying; Wen, Junjie; Niu, Hongxin; Zeng, Weisen; Bai, Yang (Frontiers in Veterinary Science, 2020)
Intestinal probiotics are a primary focus area of current medical research. Probiotics such as bifidobacteria and lactobacilli can positively impact obesity and other metabolic diseases by directly or indirectly affecting lipid metabolism. However, the precise mechanisms of these effects remain unclear. In our previous work, the novel strain Lactobacillus reuteri HI120 was isolated and identified. HI120 expresses high levels of linoleic isomerase, resulting in the production of large amounts of conjugated linoleic acid (CLA) when mixed with linoleic acid (LA). As HI120 can efficiently transform LA into CLA, the effect of HI120 on the lipid metabolism in C57BL/6 obese mice was studied and the underlying molecular mechanism was explored in vitro. The results revealed no significant change in the diet, body weight, and serum triglyceride levels in mice. However, serum cholesterol levels were significantly decreased. The underlying mechanism may involve a CLA-mediated reduction in the gene expression levels of NPC1L1, SREBP-2, and HMG-CR, resulting in reduced cholesterol synthesis and absorption. Thus, HI120 can be developed as a potential probiotic formulation. After oral administration, LA from certain food sources can be converted into CLA in the human intestine to contribute to the prevention and treatment of obesity and hyperlipidemia.